2022
DOI: 10.1136/bmjopen-2021-055754
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with intimacy in female Taiwanese patients with systemic lupus erythematosus: a cross-sectional study

Abstract: ObjectiveThe aim of this study was to investigate the association of demographic factors, clinical manifestations and disease activity of systemic lupus erythematosus (SLE) with intimate relationships in female patients with SLE.DesignThis was a cross-sectional study based on questionnaires.SettingThis study was conducted at a regional teaching hospital in southern Taiwan from April to September 2019.ParticipantsAdult patients with SLE recruited from the outpatient rheumatology clinics of the study hospital.Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
2
1
0
Order By: Relevance
“…Previous research has highlighted the influence of marital status on the QOL of SLE patients. 28 Interestingly, this study demonstrated that unmarried patients had a higher QOL, which may be associated with lower reproductive stress, aligning with findings from Wang et al and others. 29…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous research has highlighted the influence of marital status on the QOL of SLE patients. 28 Interestingly, this study demonstrated that unmarried patients had a higher QOL, which may be associated with lower reproductive stress, aligning with findings from Wang et al and others. 29…”
Section: Discussionsupporting
confidence: 91%
“…Previous research has highlighted the influence of marital status on the QOL of SLE patients. 28 Interestingly, this study demonstrated that unmarried patients had a higher QOL, which may be associated with lower reproductive stress, aligning with findings from Wang et al and others. 29 The financial burden of treatment and regular followups for SLE patients is a significant expense for families, especially considering the low per capita monthly family income.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies determined that a total SLE‐DAS score of ≤2.08 represents remission; 2.09–3.77 represents low disease activity; 3.78–7.64 represents mild disease activity; and 7.65 or more represents moderate/severe disease activity (Jesus, Matos, Henriques, Zen, Larosa, Iaccarino, da Silva, et al 2019; Jesus, Matos, Henriques, Zen, Larosa, Iaccarino, Doria, Inês, 2019). The SLE‐DAS has established acceptable reliability and validity in Caucasian, African American, Asian, and Hispanic populations (Abdelhady et al, 2021; Hsu et al, 2022; Jesus et al, 2021).…”
Section: Methodsmentioning
confidence: 99%